2020
DOI: 10.3390/antiox10010010
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Antioxidants Paraxanthine and Caffeine in Human Saliva by Electrochemical Sensing for CYP1A2 Phenotyping

Abstract: The enzyme CYP1A2 is responsible for the metabolism of numerous antioxidants in the body, including caffeine, which is transformed into paraxanthine, its main primary metabolite. Both molecules are known for their antioxidant and pro-oxidant characteristics, and the paraxanthine-to-caffeine molar ratio is a widely accepted metric for CYP1A2 phenotyping, to optimize dose–response effects in individual patients. We developed a simple, cheap and fast electrochemical based method for the simultaneous quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Anastasiadi et al [ 53 ] used an anodically pretreated glassy carbon electrode as a sensor for the determination of caffeine and paraxanthine (PX) in human saliva. According to cyclic voltammetric measurements, the authors indicated that the shape and intensity of the current response depended on the pH value of the supporting electrolyte.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anastasiadi et al [ 53 ] used an anodically pretreated glassy carbon electrode as a sensor for the determination of caffeine and paraxanthine (PX) in human saliva. According to cyclic voltammetric measurements, the authors indicated that the shape and intensity of the current response depended on the pH value of the supporting electrolyte.…”
Section: Discussionmentioning
confidence: 99%
“…The peak potential of CF did not significantly change as the pH of the supporting solution increased, in contrast to other studies [ 83 ]. In addition, Anastasiadi et al [ 53 ] concluded that in a BR buffer solution at a higher pH value of 8, a larger background current occurs due to the discharge of the electrolyte. Guan et al [ 68 ] showed that the peak potential of CF remained unchanged with the increasing pH of PBS, indicating that protons were not included in the oxidation process.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, electrochemical sensors have been developed for the detection of salivary pain killers, such as morphine (Eissa and Zourob, 2017), paracetamol (Campos et al , 2018), acetaminophen (Xie et al , 2021), tramadol (Arabali et al , 2020), aspirin (Diouf et al , 2020) and fentanyl (Mishra et al , 2022), which are widely used for pain management but also have a high potential for abuse and addiction. Similarly, electrochemical methods have been used for the a series of other pharmaceuticals, such as nicotine (Rajendran et al , 2022), diazepam (Hassan et al , 2020), cefuroxime (Kulapina et al , 2020), caffeine (Anastasiadi et al , 2020) and clonazepam (Ferreira et al , 2020).…”
Section: Analytes In Saliva and Their Electrochemical Detectionmentioning
confidence: 99%
“…It is a plant alkaloid formed by methylation of the nitrogen atom of nicotinic acid by the catalytic effect of NaMN nucleotidase, NaR nucleotidase, and nicotinate methyl transferase (Arai et al, 2015;Mohamadi et al, 2017). It is found in the range of 0.6%-1.3% in F I G U R E 2 Chemical structure of caffeine and its metabolites (Anastasiadi et al, 2021).…”
Section: Nonvolatile Components Of Coffeementioning
confidence: 99%